The Influence of E-Wom on Instagram Social Media on Interest in Buying Wedding Services at We are the Organizers Manado - Clara Angely Cambey; I Gusti Ngurah Agung Suprastayasa; I Putu Esa Widaharthana (PT FORMOSA CENDEKIA GLOBAL, 2025)
Based on Zola's survey, 75% of married couples in 2024 will use wedding organizer services, up from 70% in 2023. This study aims to examine the analysis of the influence of Electronic Word of Mouth (E-WOM) on Instagram social media on the interest in buying wedding services at We Are The Organizers Manado. The inferential quantitative method is used through data collected with documentation and questionnaires. Multiple linear regression analysis is used to test the influence of three dimensions of E-WOM: Intensity, Valence of Opinion, and Content. The results of the t-test show that Intensity and Valence of Opinion have a significant positive effect, while Content is not significant. The F test shows that the three variables simultaneously influence buying interest with a significance value of 0.000.